French art song history of a new music, 1870-1914 - Kilpatrick, Emily 1983- (University of Rochester Press, 2024)
A ground-breaking study of the musical and literary priorities, professional practices and creative interactions that shaped one of the most adventurous artforms of the Belle Époque
Title from publisher's bibliographic system (viewed on 15 Feb 2024)
Part I. Poet. Baudelaire's invitation to composers ; Song and memory in the 'Terrible Year' ; 'To the depths of the Unknown in search of the new!' -- Interlude. The poet sings -- Part II. Singer. M elodie at the crossroads ; Song, salons and the 'society singer' ; Collaboration and creative process -- Interlude. The voices of F etes galantes -- Part III. Public. Singing histories ; Reimagining song at the Conservatoire ; M elodie centre stage ; Postlude. Philosophies of composition
Keywords: Geschichte 1870-1914; Songs / France / 19th century / History and criticism; Songs / France / 20th century / History and criticism; Songs, French / 19th century / History and criticism; Songs, French / 20th century / History and criticism; Kunstlied; Frankreich